Pengaruh Program Pemutihan Pajak dan Pembebasan Bea Balik Nama Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Lodang Prananta Widya Sasana; I Gede Adi Indrawan; Ryan Hermawan (INVENTORY: JURNAL AKUNTANSI, 2021)
This study aims to prove the effect of the motor vehicle tax whitening program (PKB) and the exemption of transfer fees (BBNKB) on motor vehicle tax compliance at the SAMSAT Serpong office, South Tangerang City. The research population is all motorized vehicle users registered in SAMSAT Serpong, South Tangerang City. The method used in this study is accidental sampling, namely the technique of determining the sample by chance, that is, anyone who happens to meet the researcher. Data were collected by survey method with questionnaires, and the questionnaires were eligible for 100 questionnaires. The data analysis technique used Multiple Linear Regression Analysis. The results showed that partially there was no effect on the whitening of motor vehicle tax (PKB) and there was an effect on the exemption of transfer fees (BBNKB. However, simultaneously all variables affect the compliance of motor vehicle taxpayers in SAMSAT Serpong, South Tangerang City. This study also shows the results of the determination test, this determination explains how much the model's ability to explain the variation of the independent variable affects the dependent variable expressed in percentages.The coefficient of determination is 21.9% meaning the percentage of the influence of the independent variable on the tax whitening program (X1) and the exemption of transfer fees. (X2) to the compliance of motorized vehicle taxpayers (Y) of 21.9% while the remaining 78.1% is influenced or explained by other variables outside of the variables studied.